Optically Transparent Graphene Flakes as Nanogenerator of Microbubbles for Random Lasing in Weakly Scattering Regime. Issue 8 (25th June 2021) - Pramanik, Ashim; Biswas, Subrata; Dey, Arindam; Kumbhakar, Pathik
Abstract : The minimization of photon loss is one of the significant challenges in designing efficient random lasers (RLs). Herein, the demonstration of a 4‐(dicyanomethylene)‐2‐methyl‐6‐(4‐dimethylaminostyryl)‐4H‐pyran (DCM) dye‐based RL is made by the employment of an innovative adaptive feedback mechanism through the use of a fundamental phenomenon of total internal reflection of light in the microbubbles, generated photothermally in the presence of graphene flakes (GFs). Interestingly, here, GFs have acted simultaneously as passive scatterer and thermocatalyst for in situ generation of microbubbles in the liquid suspension of dye molecules. It is demonstrated by a simple pump‐probe photography experiment that during RL emission, the transport of photons is occurring via weak scattering in GFs followed by total internal reflection on microbubbles. Thus, RL emission at 638.4 nm is achieved with a low lasing threshold, linewidth, and moderately high quality factor of 84 W cm −2, 2 nm, and 1127, respectively. The performances of GFs in RL generation are found to be superior in comparison with those of spherical TiO2 and Ag nanoparticles. The strategy is a contemporary approach for applying a 2D material as a nanogenerator of microbubbles to achieve improved RL emission in the weakly scattering regime using an adaptive feedback approach. Abstract : Optically transparent 2D materials of graphene flakes can be simultaneously utilized as a passive scatterer of photons and nanogenerator of microbubbles providing adaptive feedback to achieve generation of narrowband random lasing in a commercial donor–acceptor‐type laser dye. The solvent polarity‐induced activation of twisted intramolecular charge transfer state of the dye molecules may lead to tunable random laser (RL) emission.